Maternal Referral at Kalabahi General Hospital : A Descriptive Study: Rujukan Maternal di Rumah Sakit Daerah Kalabahi : Sebuah Studi Deskriptif - Fuad Saddam; Putu A. A. Purbawa (Indonesian Journal of Obstetrics and Gynecology, 2020)
Abstract Objective: To find out the profile of cesarean section in dr. Zainoel Abidin Hospital since the BPJS era.Methods: This study was a descriptive-observational with retrospective design. The data were obtained in March-April 2017. We collected 3656 data from medical record period January 1st, 2014 - December 31st, 2016.Results: The finding showed there were 1,669 vaginal deliveries (45.65%) and 1,987 cesarean sections (54.35%). The most frequent causes to cesarean sections were induction failure (49.77%), cephalopelvic disproportion (14.33%), pregnancy-induced hypertension (11.21%), malpresentation (8.91), and antepartum haemorrhage (4.33%).Conclusions: The incidence of cesarean sections in dr. Zainoel Abidin Hospital since the BPJS era was 54.35%, increased by 13.29% than the year of 2011-2013 (41.06%) with the most frequent cause is induction failure (49.77%).Keywords: antepartum haemorrhage, BPJS, cesarean section, induction failure, pregnancy-induced hypertension, tertiary referral hospital. Abstrak Tujuan: Mengetahui profil persalinan seksio sesarea di RSUD dr. Zainoel Abidin Banda Aceh pada era BPJS.Metode: Penelitian deskriptif-observasional dengan desain studi retrospektif. Pengambilan data dimulai dari bulan Maret-April 2017. Sebanyak 3656 data dikumpulkan dari rekam medik periode 1 Januari 2014 - 31 Desember 2016.Hasil: Terdapat 1.669 kasus persalinan pervaginam (45,65%) dan 1.987 kasus seksio sesarea (54,35%). Indikasi terbanyak yang menyertai seksio sesarea adalah gagal induksi (49,77%), cephalopelvic disproportion (14,33%), hipertensi dalam kehamilan (11,21%), malpresentasi (8,91%), dan perdarahan antepartum (4,33%).Kesimpulan: Angka seksio sesarea di RSUD dr. Zainoel Abidin meningkat 13,29% sejak berlakunya BPJS (1 Januari 2014-31 Desember 2016) mencapai 54,35% dibandingkan tahun 2011-2013 (41,07%) dengan indikasi terbanyak gagal induksi (49,77%).Kata kunci: BPJS, gagal Induksi, hipertensi dalam kehamilan, perdarahan antepartum, RS rujukan tersier, seksio sesarea.